Mothers as advocates for healthier lifestyle behaviour environments for their children: results from INFANT 3.5-year follow-up - Christine Delisle Nyström; Karen J Campbell; David Crawford; Kylie D Hesketh (BMC, 2022)
Abstract Background The amount of time children spend outside of their home environment has increased over the past decades. Therefore, the quality of the health behaviour environments where young children spend time is likely to impact their health behaviour opportunities. The aim of this study was to describe the proportion of mothers who consider it possible to make changes in their local communities to increase opportunities for children to eat healthily, be physically active, and limit screen time exposure, as well as the proportion who have attempted to do so. The characteristics of mothers with differing advocacy beliefs and intentions were explored. Methods Cross-sectional data collected using questionnaires from 307 mothers who participated in the 3.5-year follow-up of the INFANT cluster-randomized controlled trial were used. Frequencies were used to assess the number of mothers who thought it possible to bring about change in their local communities and for the those who had attempted to do so. Binary logistic regression analyses were used to compare sociodemographic characteristics of mothers with differing responses. Results Most mothers thought it was possible to bring about change in their local community with regards to providing more opportunities for their child to eat healthily (83.7%), be physically active (90.9%) as well as limit exposure to screen time (63.5%). However, less than 19% and 11% of mothers have thought about or tried to bring about change in their child's childcare centre or local community, respectively. No sociodemographic differences were found between the mothers who thought it was possible to bring about actioning change (p-values > 0.1) or for those that have thought about change (p-values > 0.1). Conclusion As children are continuously being exposed to obesogenic environments future quantitative and qualitative studies are needed to describe how to promote parental advocacy and engagement, in order to provide children with environments that support healthy lifestyle behaviours.